Good University Governance dan Internasionalisasi Program Studi: Studi Kasus pada 2 (Dua) Program Studi di Perguruan Tinggi Negeri (PTN) dan Perguruan Tinggi Muhammadiyah (PTM) - Mutiarin, Dyah; Suswanta, Suswanta; Darumurti, Awang (Jurnal Ilmiah Administrasi Publik, 2019)
Good University Governance (GUG) is very relevant to the internationalization of any university and its department. This study compares the strategy of Department of Government Science - Muhammadiyah University of Yogyakarta (UMY), and the Department of Public Policy and Management - Gadjah Mada University (UGM). The research method used is a qualitative approach with the process of collecting data using interview techniques, documentation, observation and Focus Group Discussion (FGD). The results of this research can be seen, the variation of GUG results in encouraging internationalization, namely: focus on international reputation, focus on international networking, and focus on global branding.